Alterations in quadriceps muscle cellular and molecular properties in adults with moderate knee osteoarthritis. Issue 10 (October 2018) - Noehren, B.; Kosmac, K.; Walton, R.G.; Murach, K.A.; Lyles, M.F.; Loeser, R.F.; Peterson, C.A.; Messier, S.P.
Summary: Objective: Quadriceps muscle weakness is common in knee osteoarthritis (OA). While pain, disuse, and atrophy are commonly cited causes for muscle weakness in OA, emerging evidence suggests changes in muscle quality also occur. Alterations in muscle quality are not well understood, but likely include both cellular and morphologic adaptions. The purpose of this study was to conduct the first cellular-level analysis of the vastus lateralis in adults with moderate knee OA. Methods: Vastus lateralis biopsies were obtained from 24 subjects with moderate knee OA and 15 healthy controls. Quadriceps strength, muscle fiber cross sectional area (CSA), fiber type distribution, extracellular matrix (ECM) content, satellite cell abundance, and profibrotic gene expression were assessed. Results: Relative to controls, quadriceps strength was significantly lower in OA subjects (OA 62.23, 50.67–73.8 Nm vs 91.46, 75.91–107.0 Nm, P  = 0.003) despite no difference in fiber CSA. OA subjects had significantly fewer Type I fibers (OA 41.51, 35.56–47.47% vs 53.07, 44.86–61.29%, P  = 0.022) and more hybrid IIa/x fibers (OA 24.61, 20.61–28.61% vs 16.4, 11.60–21.20%, P  = 0.009). Significantly greater ECM content, lower satellite cell density, and higher profibrotic gene expression was observed with OA, and muscle collagen content was inversely correlated to strength and satellite cell (SC) density. Conclusion: Lower quadriceps function with moderate OA may not result from fiber size impairments, but is associated with ECM expansion. Impaired satellite cell density, high profibrotic gene expression, and a slow-to-fast fiber type transition may contribute to reduced muscle quality in OA. These findings can help guide therapeutic interventions to enhance muscle function with OA.